Post Conflict Rebuilding: An Exploration of Destination Brand Recovery Strategies. - Qureshi, Reyaz A.; Dada, Zubair A. (Advances in Social Sciences Research Journal, 2019)
The tectonic shifts that emerged towards the end of the Cold War have metamorphosed the international security agenda. The degeneration of the Soviet Union, the surfacing of nationalist independence movements across the post-communist horizon, and the pulling out of superpower support to prop up friendly regimes throughout the third world unleashed new forces that, among other things, resulted in a considerable augmentation in the number of intra-state wars during the 1990s. By September 11, 2001 at the very latest, it became noticeably comprehensible that intra-state conflicts – and their correlation with fragile and failing states – represent not only a major humanitarian apprehension but also a considerable threat to regional and global security. As a result, one of the fundamental challenges facing the international community at the moment involves the prevention and resolution of violent conflicts. Structured tourism in Sri Lanka was inducted in 1966 and Sri Lanka experienced 16 years of swift spreading out of its tourism sector between 1967 and 1982. Arrivals amplified at an average annual rate of more than 20 per cent. However, the tourism trade was sternly impacted by the ethnic violence in mid-1983 and consequently both by the long-dragging ethnic conflict in the North and East of the island and due to insurrection behavior which occurred in areas closer to the tourism operations on the West and South coasts. Therefore, international tourist arrivals kept declining each year placing the trade on a diminishing track. Thus, a political unrest can potentially produce a significant catastrophe since it is capable of impacting negatively the smooth operations of the tourism industry. This paper explores the implications of branding destinations in a post-conflict scenario and the opportunities thereof. Destination branding literature insists that every destination should incorporate crisis management strategies in its tourism planning protocols, management exercises and destination marketing campaigns. This paper proposes that destination branding should be coupled with crisis management strategies for leveraging an opportunity out of crisis, so that, tourism can be a critical catalyst in post conflict reconstruction and overcoming the negative imagery and distrust which still impedes the Sri Lanka’s ability to achieve greater political integration and tourism prosperity in an increasingly globalized world.